Pengembangan Media Pembelajaran Ular Tangga Bermuatan Aqidah: Studi Pada Materi Iman Kepada Hari Akhir di MTs Darul Amin Palangka Raya - Rowina, Sinta; Jennah, Rodhatul; Gofur, Abdul (Kamaya: Jurnal Ilmu Agama, 2025)
Based on the results of the researcher's observations, there are problems in the use of conventional and passive learning media. In solving these problems, the researcher developed a snake and ladder game media on the material of faith in the hereafter which is the 5th pillar of faith. Limited distribution was only carried out at MTs Darul Amin Palangkaraya school. Another goal is to find out whether the snake and ladder game media is suitable for use as a learning medium. This study uses a research and development method with the 4D Thiagaraja model. This stage consists of define, design, develop, and disseminate. Based on the results of the study, the results of the validation of material experts obtained an average percentage of 87% with the criteria "Very Eligible" for use, the results of the validation of media experts obtained an average percentage of 98.6% with the criteria "Very Eligible" for use, the results of educator responses obtained an average percentage of 100% with the criteria "Very Eligible" for use. This research and development is designed to help solve the difficulties of teachers and students, this creative and fun learning media has a touch of technology and is easy to operate by the teacher concerned in the learning process, this can create a pleasant classroom atmosphere and can encourage students to participate directly in the teaching and learning process, belief in the hereafter provides self-awareness of responsibility and encourages noble behavior and avoids sin.